THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN DEVELOPING THE CREATIVE-PRACTICAL ACTIVITY SKILLS OF FUTURE PRIMARY SCHOOL TEACHERS: https://doi.org/10.5281/zenodo.15795846 - Mamadiyorov, Jamol (Journal of Contemporary World Studies, 2025)
This article presents methods for developing the creative-practical activity skills of future primary school teachers using various tools.